Spondin2 is a new prognostic biomarker for lung adenocarcinoma - Yuan, Xiaopeng (Oncotarget, 2017)
Spondin 2 (SPON2) is a member of the F-spondin superfamily of genes that encode an extracellular matrix protein. SPON2 has been identified by mRNA differential display screening of cancerous and noncancerous lung cell lines in vitro [1], however, its role in pulmonary adenocarcinoma (ADC) patients remains unclear. In our study, we evaluated whether SPON2 can be used as a biomarker for the diagnosis of pulmonary ADC and any association between SPON2 protein levels and clinicopathological characteristics. Firstly, the mRNA levels of SPON2 in pulmonary ADCs and normal adjacent tissue samples were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR) (n = 60) assay and the expression of SPON2 protein were detected by tissue microarray immunohistochemistry analysis (TMA-IHC) (n = 280). Overexpression of SPON2 protein in cancerous tissues was associated with the clinical characteristics of ADC patients and their overall survival. Levels of SPON2 mRNA and protein were significantly expressed higher in ADC tissues than in adjacent normal tissues. Finally, through univariate and multivariate regression analysis, we found that overexpression of SPON2 protein levels correlates with differentiation, positive lymph nodes metastasis, higher serum carcinoembryonic antigen (CEA) level and poor overall survival. Overexpression of SPON2 protein is an independent prognostic biomarker in ADC patients. Our data revealed that SPON2 played an oncogene role in ADC development and progression. Inhibiting SPON2 might represent a new strategy for pulmonary ADC.